Morphometric analysis of some properties of the river network of the Salmana Basin and its secondary basins - Shrhaan, Zahraa Kareem; Alibrahimi, Suhaila Najem (Al-Adab Journal, 2022)
Morphometric analysis is defined as quantitative analysis of river drainage systems in the surveyor unit of the drainage basin, Because it includes a group of river mattresses that have properties that can be quantifiable and then analyzed, categorized and arranged, this means that the morphological study is a process of linking the different characteristics of the drainage network with each other and linking them to the hydrological characteristics of the waterway, and therefore it combines form and process) in a quantitative framework (Saad Ajil Mubarak, 2009,130),and The river basin is known as the area where the water gathers to pour into a particular stream or river, and the importance of morphometric analysis comes in identifying the characteristics of the river drainage system, as well as the processes affecting the formation of the earth's surface, identifying hydrological characteristics and knowing the extent of development of the river basin network, the morphological characteristics of the main basins have been identified, which were represented by the basins (main Salmana, Nashak, Eastern, Gattan, Southern, the number of basins (5) basins including a head basin and four secondary basins.